European competitiveness and sustainable development – A policy-oriented response to "Rethinking the role of the EU in enhancing European competitiveness". Issue 5 (21st May 2021) - Aiginger, Karl
Abstract : Purpose: The world order is changing, with the lead of the US waning, along with its reduced commitment to rule-based multilateralism during the past administration. China is on the way to becoming number one again, investing abroad with primarily egoistic motives and steered by an authoritarian domestic regime. Meanwhile, the EU is striving for a new geopolitical role, while becoming more heterogenous. Design/methodology/approach: The paper measures performance and competitiveness not only according to conventional criteria but also based on broader welfare indicators. The ultimate aim of competitiveness is to deliver well-being. Decentralized local strategies are presented, but also the need for guidance by societal goals. Findings: What we measure matters. The EU is underperforming in per capita GDP and failing to close the gap in labour productivity towards the frontier defined by the USA. But it is leading in environmental and social indicators, has an accessible health system and provides increasing longevity. This performance nevertheless has to be improved, if climate goals should be fulfilled and upcoming new inequalities addressed. Originality/value: Localization and place-based strategies have advantages, but also harper the danger that negative spillovers may not be minimized and positive not used. Innovation is a search process but has to be directed by goals in Europe and globally. Otherwise, change incurs high costs and many losers, fostering nationalism and populistic calls to return to a past glory that never existed.